2019
DOI: 10.3389/fnins.2019.00534
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Structural Pattern Predicting Medication Response in Herpes Zoster Patients Using Multivoxel Pattern Analysis

Abstract: Herpes zoster (HZ) can cause a blistering skin rash with severe neuropathic pain. Pharmacotherapy is the most common treatment for HZ patients. However, most patients are usually the elderly or those that are immunocompromised, and thus often suffer from side effects or easily get intractable post-herpetic neuralgia (PHN) if medication fails. It is challenging for clinicians to tailor treatment to patients, due to the lack of prognosis information on the neurological pathogenesis that underlies HZ. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(88 reference statements)
0
8
1
Order By: Relevance
“…The SVM classifier performed between HZ and PHN patients had a classification accuracy of 61.54%. We did not achieve as high a classification accuracy as in previous studies (31,46). It should be noted that, in our study, all patients have taken pregabalin and amitriptyline to alleviate the pain intensity before the MRI scan.…”
Section: Identification Of Patients With Phn From Hc and Patients Witcontrasting
confidence: 79%
See 1 more Smart Citation
“…The SVM classifier performed between HZ and PHN patients had a classification accuracy of 61.54%. We did not achieve as high a classification accuracy as in previous studies (31,46). It should be noted that, in our study, all patients have taken pregabalin and amitriptyline to alleviate the pain intensity before the MRI scan.…”
Section: Identification Of Patients With Phn From Hc and Patients Witcontrasting
confidence: 79%
“…For patients with neuropathic pain, one previous neuroimaging study has found that the voxelmirrored homotopic connectivity in the dorsolateral prefrontal cortex, precuneus, and PCC discriminated between patients with PHN and healthy subjects (31). Our recent study measuring gray matter volume found that alterations in several brain regions, including the middle frontal cortex, ACC, precuneus, and cuneus, had a significant predictive power to classify HZ patients with different responses to medications (46). Along with these findings, our observations suggested that the frontal gyrus and the precuneus have a significant predictive power to distinguish neuropathic pain patients from the healthy controls.…”
Section: Identification Of Patients With Phn From Hc and Patients Witmentioning
confidence: 82%
“…Since Cortes and Vapnik proposed the Support Vector Machine (SVM) technique, 29 it has been widely used in brain science research to solve the binary classification problem 27,30–38 . The decision function of SVM is shown as follows:Yxk=signfalse∑i=1Kαiyi.Kxk,xi+bwhere Ƙ represents the kernel function.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the inputted zALFF maps were masked with an Anatomical Automatic Labeling 116 gray matter atlas to remove the signals of white matter and cerebrospinal fluid and reduce the computation burdens. We combined the searchlight algorithm (42) and principal component analysis (PCA) to conduct feature selection referencing the previous studies (43)(44)(45)(46). Briefly, at each voxel (Vi), a spherical cluster with a 9-mm radius was defined centering at Vi, and the value of each voxel within the spherical cluster was extracted to generate the feature matrices.…”
Section: Study 1: Pattern Classification Of Patients With Mwoa and Hsmentioning
confidence: 99%
“…The meaningful classifying features were defined as those clusters with a minimum accuracy of 70% and more than 50 contiguous voxels. Same to the previous studies (44,45), the accuracy of each cluster was determined by its peak accuracy.…”
Section: Study 1: Pattern Classification Of Patients With Mwoa and Hsmentioning
confidence: 99%